Morphine-mediated release of astrocyte-derived extracellular vesicle miR-23a induces loss of pericyte coverage at the blood-brain barrier: Implications for neuroinflammation - Liao, Ke; Niu, Fang; Hu, Guoku; Buch, Shilpa (Frontiers in Cell and Developmental Biology, 2022)
Opioids such as morphine are the most potent and efficacious drugs currently available for pain management. Paradoxically, opioids have also been implicated in inducing neuroinflammation and associated neurocognitive decline. Pericytes, a critical component of the neurovascular unit (NVU), are centrally positioned between endothelial cells and astrocytes, maintaining the blood-brain barrier (BBB) functioning and regulating neuroinflammation by controlling monocyte influx under various pathological conditions. The role of pericytes in morphine-mediated neuroinflammation however, has received less attention, especially in the context of how pericytes crosstalk with other central nervous systems (CNS) cells. The current study was undertaken to examine the effect of miRNAs released from morphine-stimulated human primary astrocyte-derived extracellular vesicles (morphine-ADEVs) in mediating pericyte loss at the BBB, leading, in turn, to increased influx of peripheral monocytes. Our findings suggested that in human primary astrocytes morphine-mediated upregulation and release of of miR-23a in ADEVs involving the heterogeneous nuclear ribonucleoprotein complext A2/B1 (hnRNP A2/B1), and through action of morphine via mu opioid receptor. We further demonstrated that miR-23a in morpphine-ADEVs could be taken up by pericytes, resulting, in turn, to downregulation of PTEN expression, ultimately leading to increaesd pericyte migration. Furthermore, both overexpression of PTEN and blocking the miR-23a target site at PTEN 3UTR (by transfecting miR-23a-PTEN target protector), attenuated morphine-ADEV-mediated pericyte migration. We also demonstrated in the microvessels isolated from morphine-adminsitered mice, there were lesser numbers of PDGFβR+ pericytes co-localizing with CD31+ brain endothelial cells compared with those from saline mice. In line with these observations, we also observed increased loss of pericytes and a concomitantly increased influx of monocytes in the brains of morphine-administered pericyte-labeled NG2-DsRed mice compared with saline mice. In conclusion, our findings indicate that morphine-ADEVs mediated loss of pericyte coverage at the brain endothelium, thereby increasing the influx of peripheral monocytes in the CNS, leading to neuroinflammation.